NUMERICAL MODELING THE INTERACTION OF A MAGNETIC FIELD WITH A CYLINDRICAL MAGNETIC FLUID LAYER - V. K. Polevikov; V. T. Erofeenko (Informatika)
A combined method of finite differences and boundary elements is applied to solve a nonlinear conjugate problem of magnetostatics describing, the interaction of a uniform magnetic field with a cylindrical magnetic fluid layer. Magnetic permeability of the fluid is considered to be a non-linearly dependent on the magnetic field intensity. Shielding properties of a cylindrical thick-walled magneticfluid layer, depending on the external magnetic field intensity, are investigated. A shielding effectiveness factor is calculated.